Group A Streptococci-Associated Necrotizing Fasciitis following Cat Bite in an Immunocompromised Patient - Sudheer Nambiar; Asha Karippot; Joe Devasahayam; Tony Oliver (Case Reports in Critical Care)
Necrotizing soft tissue infections are characterized clinically by fulminant tissue destruction, systemic signs of toxicity, and high mortality. Accurate diagnosis and appropriate treatment must include early surgical intervention and antibiotic therapy. Mortality rate is very high and could be even higher in an immunocompromised host. We present a 57-year-old female with history of rheumatoid arthritis on oral corticosteroid and methotrexate therapy with painful swelling of the left hand following a cat bite that was diagnosed as having group A streptococcus pyogenes-associated necrotizing fasciitis. Treatment with ampicillin-sulbactam, Clindamycin, and surgical debridement was performed. In spite of all the adequate therapy she succumbed to death from streptococcal toxic shock and related complications after thirty-two days of treatment in intensive care unit. Necrotizing fasciitis is an uncommon but life-threatening complication in immunocompromised hosts. Tissue infections in cat bite wounds are commonly caused by pathogenic bacterium known as Pasteurella multocida. Group A streptococcal infections are not reported following cat bites. A high index of suspicion must be maintained to suspect group A streptococcal associated necrotizing fasciitis following cat bites and an early medical and surgical intervention should be made for any best possible outcome.